Dinamika Historis Konstitusional, Sosial Politik, Kultural, dan Konteks Kontemporer Penegakan Hukum - Nadia Alkhalifi Dwi Ramadhani; Syela Indah Rahmawati; Nessa Nelsanda; Rachel Zalfa Zahiyah Azzahra; Yunisius Gagut; Natasya Devaverdiani; Aulia Pasya Nagita Za'ara; Syahril Afifuddin Amrullah; Suyono Suyono (Jurnal Kajian dan Penelitian Umum, 2024)
Law enforcement in Indonesia faces a range of challenges, including corrupt practices, social injustice, and weak capacity of law enforcement officials, which hinder the achievement of a safe, orderly, just, and prosperous society. This research aims to analyze the historical, socio-political, and cultural dynamics that affect law enforcement in Indonesia, as well as to identify solutions to strengthen a just legal system. The method used is literature research with a qualitative approach, collecting data from related literature and analyzing relevant legal concepts and social dynamics. The findings of the study show that fair enforcement of the law is essential to ensure justice not only in terms of legal, but also social and moral, considering the influence of religious, customary, and state laws. In addition, the politicization of the law is a big challenge. The implications of this research are the need for legal system reform, strengthening the capacity of law enforcement officials, increasing access to justice, and the use of technology to increase transparency and efficiency. Collaboration between the government, law enforcement, and the public is also key to creating a more responsive and fair legal system in Indonesia.